ChemInform Abstract: Step‐Economical Access to Valuable Weinreb Amide 2, 5‐Disubstituted Pyrrolidines by a Sequential One‐Pot Two‐Directional Cross‐Metathesis/Cyclizing Aza‐Michael Process. Issue 29 (1st July 2013) - Boufroura, Hamza; Mauduit, Marc; Drege, Emmanuelle; Joseph, Delphine
Abstract: This is the first two‐directional homologating double cross‐metathesis of unfunctionalized 1, 5‐hexadiene.